Bacteriological quality of fresh and processed black soldier fly Hermetia illucens larvae reared on chicken manure in Kitwe, Zambia - Prudence Mapiki; Ester Laiser; Joyce Mufungwe; Misheck Shawa; Mazuba Siamujompa; Todd Johnson; Ngawo Namukonde; Phenny Mwaanga; Bernard Mudenda Hang'ombe (Microbiology Spectrum)
ABSTRACT Black soldier fly larvae (BSFL) have high nutrient content and are rapidly becoming an alternative protein source for animal feed. However, microbial contamination is a potential risk due to the environment in which they are reared. This study assessed the bacteriological quality of fresh and processed BSFL by comparing the processed BSFL using two traditional methods (oven-dried and sun-dried), on their effectiveness at reducing the bacterial load and further elucidated bacterial composition. PCR was used to identify extended-spectrum β-lactamase (ESBL) and mecA genes in Escherichia coli and Staphylococcus spp., respectively. A total of 51 fresh BSFL samples were collected from a commercial poultry farm in Kitwe, Zambia. The results showed various bacterial genera, with a higher diversity among gram-positive isolates. The comparison of the effectiveness of two traditional processing methods for BSFL, sun-drying and oven-drying, showed that both methods significantly reduced the bacterial load, with oven-drying causing a larger reduction. While various genera were identified, we focused on E. coli and Staphylococcus spp. This is because some E. coli harbor ESBLs that hydrolyze β-lactam antibiotics like cephalosporins and penicillin, leading to resistance. Similarly, the genus Staphylococcus was selected since some strains are potentially pathogenic and contain the mecA gene that encodes resistance to β-lactam antibiotics. Molecular characterization of the isolated strains revealed blaCTX-M and blaTEM genes among E. coli, but the mecA gene was not detected among Staphylococcus. This study revealed that BSFL harbor bacteria of zoonotic significance, emphasizing the need for good processing methods to eliminate potential risks.IMPORTANCEIsolation and identification of Escherichia coli and Staphylococcus spp. in processed black soldier fly larvae (BSFL) samples meant for animal feed indicate insufficient processing methods and pose a public health risk. For instance, some E. coli harbor extended-spectrum β-lactamases (ESBLs) that hydrolyze β-lactam antibiotics like cephalosporins and penicillin, leading to resistance. In addition, some E. coli commensals can transfer antimicrobial resistance genes to pathogenic bacteria through horizontal gene transfer using various mobile genetic elements, leading to resistance. Similarly, for Staphylococcus spp., some strains of the genus Staphylococcus are potentially pathogenic and contain the mecA gene that encodes resistance to β-lactam antibiotics. In this study, we used PCR to screen E. coli isolates for the two commonly reported ESBL genes in Zambia, blaCTX-M and blaTEM, and Sanger sequencing was used to reveal blaCTX-M gene alleles. Our results highlight the importance of using adequate processing methods for BSFL to eliminate potential health risks to animal feed.